Observation of Dirac monopoles in a synthetic magnetic field - Ray, M. W.; Ruokokoski, E.; Kandel, S.; Möttönen, M.; Hall, D. S. (Nature (London), 2014)
Dirac magnetic monopoles are created, directly imaged and identified in real space in the synthetic magnetic field produced by a spinor Bose–Einstein condensate. Dirac action creates elusive monopoles Ever since Dirac developed a comprehensive theory of magnetic monopoles in 1931, physicists have been eager to isolate these hypothetical particles featuring a north or south pole only. Although magnetic monopole analogues have been found in spin ices and other exotic systems, no Dirac monopoles have been observed directly within a medium described by a quantum field. But now David Hall and colleagues report the experimental observation of Dirac monopoles in the synthetic magnetic field produced by a spinor Bose–Einstein condensate. The authors obtain real-space images of monopoles at the termini of vortex lines within the condensate, providing evidence of the existence of Dirac monopoles. The creation and manipulation of Dirac monopoles in a controlled environment opens up a wide range of experimental and theoretical investigations. Magnetic monopoles—particles that behave as isolated north or south magnetic poles—have been the subject of speculation since the first detailed observations of magnetism several hundred years ago 1 . Numerous theoretical investigations and hitherto unsuccessful experimental searches 2 have followed Dirac’s 1931 development of a theory of monopoles consistent with both quantum mechanics and the gauge invariance of the electromagnetic field 3 . The existence of even a single Dirac magnetic monopole would have far-reaching physical consequences, most famously explaining the quantization of electric charge 3 , 4 . Although analogues of magnetic monopoles have been found in exotic spin ices 5 , 6 and other systems 7 , 8 , 9 , there has been no direct experimental observation of Dirac monopoles within a medium described by a quantum field, such as superfluid helium-3 (refs 10 , 11 , 12 , 13 ). Here we demonstrate the controlled creation 14 of Dirac monopoles in the synthetic magnetic field produced by a spinor Bose–Einstein condensate. Monopoles are identified, in both experiments and matching numerical simulations, at the termini of vortex lines within the condensate. By directly imaging such a vortex line, the presence of a monopole may be discerned from the experimental data alone. These real-space images provide conclusive and long-awaited experimental evidence of the existence of Dirac monopoles. Our result provides an unprecedented opportunity to observe and manipulate these quantum mechanical entities in a controlled environment.